Analisis Efektivitas Pemanfaatan Aset Wakaf dalam Peningkatan Kualitas Pendidikan Pesantren - Nasution, Riska Amelia; Nasution, Yenni Samri Juliati (Polyscopia, 2025)
The utilization of waqf assets represents a strategic solution to support the improvement of Islamic boarding school (pesantren) education, which often grapples with challenges such as limited financial resources and infrastructure. This study aims to analyze the effectiveness of waqf asset management in enhancing the quality of education in pesantren, focusing on asset management practices, resource allocation, and their impact on learning outcomes. Employing a qualitative descriptive approach, the research uses case studies of several pesantren in Indonesia. Data were collected through in-depth interviews, field observations, and analysis of documents related to waqf asset management. The findings reveal that professional and transparent management of waqf assets significantly contributes to improving educational facilities, enhancing teacher welfare, and advancing competency-based curricula. This study concludes by emphasizing the importance of strengthening waqf asset governance through collaboration between pesantren, government bodies, and philanthropic institutions. The authors recommend the development of national policies to optimize waqf assets as a sustainable instrument for advancing pesantren education.